2013
DOI: 10.1111/ruso.12004
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Marcellus Shale Gas Development in Pennsylvania and Local Perceptions of Risk and Opportunity

Abstract: Recent advances in gas and oil drilling technology have led to dramatic boomtown development in many rural areas that have endured extended periods of economic decline. In Pennsylvania's Marcellus gas fields, the recent development of unconventional shale gas resources has not been without controversy. It has been variously framed as a major opportunity for economic revitalization at the local and regional levels and energy independence at the national level, but also as a significant environmental risk, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 31 publications
1
87
0
Order By: Relevance
“…[6,10]). While these economic benefits are far from agreed-upon [39,34], the point we wish to emphasize here is that the potential for these benefits has affected the discourse surrounding shale gas development [19] in a way that differs from the UK.…”
Section: Introductionmentioning
confidence: 99%
“…[6,10]). While these economic benefits are far from agreed-upon [39,34], the point we wish to emphasize here is that the potential for these benefits has affected the discourse surrounding shale gas development [19] in a way that differs from the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid population changes (derived from the Community Impact of Unconventional gas development: Summary and Challenges DOI: 10.9790/0837-2108105766 www.iosrjournals.org 64 | Page workers on the industrial site accompanied by their families) can put more pressure on local schools, which in small communities cannot accommodate the needs. Others [36] have found however found that school in the affected counties in Pennsylvania did not experience a net increase in enrollment associated with unconventional gas development. This can be explained by the fact that most of the workers on the drilling sites do not bring their family to live with them in the proximity of the operation site.…”
Section: Assessment Of the Social Impact Of Unconventional Gasmentioning
confidence: 90%
“…This can be explained by the fact that most of the workers on the drilling sites do not bring their family to live with them in the proximity of the operation site. Workers on the operation site require housing facilities, with some being addressed by the companies performing the operations who build dormitories for the workers [36], but this fails to meet the demand, putting pressure on the local services. A lack of affordable, quality housing has been identified as one of the most critical early impacts unconventional gas development in the United States, especially in small rural communities [5].…”
Section: Assessment Of the Social Impact Of Unconventional Gasmentioning
confidence: 99%
“…These possible impacts include: disruption of social cohesion, competition over water between oil and gas companies and existing lawful water users in the Karoo; securing access to water and sanitation for previously disadvantaged communities in the face of competing demands presented by fracking operations; the potential health risks associated with lack of access to water and adequate sanitation in vulnerable communities; in-migration and higher population density in ecologically sensitive and water scarce areas Broderick et al, 2011;Dolesh, 2011;Kargbo et al, 2010;Schafft et al, 2013 andWarren, 2013). Even a social-economic benefit such as job creation may be contentious as it is not guaranteed that jobs created in the oil and gas sector will offset job losses in other sectors such as the agricultural sector resulting in displacement of people (Dolesh, 2011;Kargbo et al, 2010;Schafft et al, 2013 andWarren, 2013). Therefore, the dynamic and multi-faceted socio-economic impacts of unconventional gas extraction in communities in areas where basic resources such as water are already under pressure should be identified and linked with wider developmental and environmental concerns.…”
Section: Possible Impacts Associated With Uog Extractionmentioning
confidence: 99%